SMALL AND MEDIUM MICRO ENTREPRISES INNOVATION STRATEGIES IN EFFORTS TO FACE THE INDUSTRY REVOLUTION 4.0 - Tranggono -; Egan Evanzha Yudha Amriel, S.MN., M.M; Endang Sholihatin; Nanang Haryono (Journal of Economics, Business, and Government Challenges, 2021)
Micro, small and medium enterprises still rely on conventional ways of doing business. On the other hand, rapid digitalization is integrated with the economy and trade, giving birth to the industrial revolution 4.0. If micro, small and medium enterprises do not want to innovate, they will be disrupted. The research objectives are to describe the innovation strategies of micro, small and medium enterprises in increasing competitiveness in facing the industrial revolution 4.0; and also identify factors that hinder the innovation of micro, small and medium enterprises in increasing competitiveness in facing the industrial revolution 4.0. The method used in this research is qualitative. The research location is in the area of ​​micro, small and medium enterprises in Gresik Regency and Sidoarjo Regency. The conclusion of this research is(a) innovation strategies for micro, small and medium enterprises in increasing competitiveness in facing the industrial revolution 4.0 through marketing with e-commerce marketing through social networking media. One of the strategies is product innovation.(b) Furthermore, the factors that hinder innovation are human resources, capital to innovate, a narrow owner's mindset, and the use of technology that is still simple. lack of strategic partners for innovation, managementmicro small and Medium Enterprises who are kinship and less professional, and lack of permits micro small and Medium Enterprises.